Array‐based "Chemical Nose" Sensing in Diagnostics and Drug Discovery. Issue 16 (20th February 2019) - Geng, Yingying; Peveler, William J.; Rotello, Vincent M.
Abstract: Array‐based sensor "chemical nose/tongue" platforms are inspired by the mammalian olfactory system. Multiple sensor elements in these devices selectively interact with target analytes, producing a distinct pattern of response and enabling analyte identification. This approach offers unique opportunities relative to "traditional" highly specific sensor elements such as antibodies. Array‐based sensors excel at distinguishing small changes in complex mixtures, and this capability is being leveraged for chemical biology studies and clinical pathology, enabled by a diverse toolkit of new molecular, bioconjugate and nanomaterial technologies. Innovation in the design and analysis of arrays provides a robust set of tools for advancing biomedical goals, including precision medicine. Abstract : Smelling diseases : Array‐based sensor "chemical nose" platforms are inspired by the mammalian olfactory system. Multiple sensor elements in these devices selectively interact with target analytes, producing a distinct pattern of response. Innovation in the design and analysis of arrays provides a robust set of tools for advancing biomedical goals, including precision medicine.